PEMIKIRAN NAWAL EL SAADAWI DAN RELEVANSINYA DENGAN NILAI-NILAI KEISLAMAN DALAM AL-QURAN - Yulita Putri; Abid Nurhuda (ISLAMIKA, 2023)
Egypt is a very patriarchal country both structurally and culturally, in general, society still places women second in aspects of life so that Islamic reformers emerged there, one of whom was Nawal El Sadawi who fought for the values of justice and equality. So the purpose of this research is to describe Nawal El Sadawi's thoughts and their relevance to Islamic values in the Koran. The method used is descriptive qualitative with literature study techniques, then the data is collected after that the contents are analyzed and the last is the conclusion. The results of the study show that Nawal El Sadawi's thoughts are justice and equality between men and women. These narratives are often considered sarcastic, sharp, to the point of being out of line with Islam, even though in essence these values are so Islamic because they are relevant to what is contained in the Qur'an.